ANALISIS PROBLEMATIKA GURU DALAM MENANAMKAN KARAKTER TANGGUNG JAWAB DAN DISIPLIN PADA SISWA KELAS IV DAN V SD INPRES 3/77 SANREGO DESA SANREGO, KECAMATAN KAHU KABUPATEN BONE - Sudarto Sudarto; Rosmalah Rosmalah; Muh.Zefri Awal (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
This research is a descriptive qualitative research type that aims to find out the problems of teachers in instilling the responsibility and discipline character of grades IV and V at SD Inpres 3/77 Sanrego, Sanrego Village, Kahu District, Bone Regency. The subjects in this study were the headmaster and homeroom teachers for grades IV and V at SD Inpres 3/77 Sanrego. Data collection techniques were carried out by interview techniques. Data analysis techniques were carried out in three stages, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that the teacher's problems in instilling the responsibility and discipline character include: low student motivation, lack of family and environmental support, the teacher's inconsistency in giving examples, the lack of agreement of all teachers in instilling character and students' difficulty accepting change and making changes, namely how to become a student with responsible and disciplined character. Conclusion: teacher problems in instilling the responsibility and discipline character in the form of obstacles and difficulties mainly come from student, parent and teacher factors